Absolute, pressure-dependent validation of a calibration-free, airborne laser hygrometer transfer standard (SEALDH-II) from 5 to 1200 ppmv using a metrological humidity generator - Buchholz, Bernhard; Ebert, Volker (Atmospheric measurement techniques, 2018)
Abstract. Highly accurate water vapor measurements are indispensable for understanding a variety of scientific questions as well as industrial processes. While in metrology water vapor concentrations can be defined, generated, and measured with relative uncertainties in the single percentage range, field-deployable airborne instruments deviate even under quasistatic laboratory conditions up to 10-20 %. The novel SEALDH-II hygrometer, a calibration-free, tuneable diode laser spectrometer, bridges this gap by implementing a new holistic concept to achieve higher accuracy levels in the field. We present in this paper the absolute validation of SEALDH-II at a traceable humidity generator during 23 days of permanent operation at 15 different H2O mole fraction levels between 5 and 1200 ppmv. At each mole fraction level, we studied the pressure dependence at six different gas pressures between 65 and 950 hPa. Further, we describe the setup for this metrological validation, the challenges to overcome when assessing water vapor measurements on a high accuracy level, and the comparison results. With this validation, SEALDH-II is the first airborne, metrologically validated humidity transfer standard which links several scientific airborne and laboratory measurement campaigns to the international metrological water vapor scale.
Gesehen am 02.12.2020